Simultaneous sacchariﬁcation and fermentation (SSF) of rice cooker wastewater by using Aspergillus niger and Saccharomyces cerevisiae for ethanol production - Masoud Hatami; Habibollah Younesi; Nader Bahramifar (Journal of Applied Research in Water and Wastewater, 2015)
This work examined the simultaneous sacchariﬁcation and fermentation (SSF) process for the biological conversion rice wastewater into ethanol using co-culture of Aspergillus niger (A. niger) and Saccharomyces cerevisiae (S. cerevisiae) in batch condition. In this study, The A. niger and S. cerevisiae were used for hydrolysis and production of ethanol from rice wastewater, respectively. The Effects of fermentation parameters such as pH (4, 4.5, 5 and 5.5), temperature (25, 30, 35 and 40 °C), incubation period (12 to 72 h), incubation time (12 to 72 h) and nitrogen source on SSF were evaluated. The results showed that among the optimal parameters of pH 5, temperature 35 oC, incubation period 36 h, incubation time 36 h and nitrogen source of (NH4)2SO4 were obtained in ethanol production by SSF process. Under these optimized conditions, maximum ethanol production and product yield were 16.97 g/l and 0.36 g/g, respectively.